Do the Implementation of Green Practices Initiatives in Starbucks Increase the Number of Tourists to a City? (Study Case of Starbucks in Pontianak) - Malini, Helma (Samarinda State Polytechnic, 2021)
This study aims to examine the influence of Eco-friendly Practices, Green Brand Image and Green Initiatives on the number of tourists visiting Pontianak. The type of research used in this research is quantitative by using a survey method wherein survey research using a questionnaire that will be given to respondents according to predetermined criteria. The population of this research is the consumer who has visited, received offers and made purchase decisions at least two times for Starbucks products with the sample is 100 respondents. The technique used is non-probability sampling, which is a sampling technique that does not provide equal opportunities for each element or member of the population to be selected as samples, and the purposive sampling method is a sampling technique with certain considerations. The data will be analyzed by using PASW Statistics 18 software application and the method used is multiple linear regression with the variables of Eco-Friendly Practices, Green Brand Image and Green Initiatives, and several tourists. The results show that Eco-Friendly Practices, Green Brand Image and Green Initiatives have a significant effect number of tourists visiting Pontianak.